A comunidade discursiva dos booktubers: percursos de análise de comunidades virtuais - Vieira, Wesley Linhares (2018)
In this research, the theoretical-methodological proposal from John M. Swales (1990; 1992; 1998) was used for the analysis of discourse communities, and the methodological perspectives of virtual ethnography (HINE, 2000) with the intention of understanding the communicative singularity of the booktube group. Hence, the theoretical approach chosen assumes that the production of a genre is intrinsically related to the social and historical conditions in which the users and producers are inserted. As for the notion of what a discourse community is, we rely, theoretically, on Swales (1990; 1992; 1998), the author who investigated the necessary criteria for a group to be classified as a discourse community. We also relied on the studies conducted by Biasi-Rodrigues (1998), Bernardino (2000), Araújo (2003), Gaede (2003), Catunda (2004) and Lima (2008) in order to understand how a community whose practices are born on the web is different from those studied by these authors. Concerning the methodology used, we applied the principles of the virtual ethnography from Hine (2000), which considers that the study of events that take place on the internet benefit the comprehension of individuals and their practices. Thus, we initially analysed one hundred (100) booktube channels and identified three (03): two (02) experienced booktubers and one (01) beginner, from whom we extracted the necessary netnographic materials to better understand the complexity of this virtual group, aim of this research.